2007
DOI: 10.1126/science.1143906
|View full text |Cite
|
Sign up to set email alerts
|

Glaciers Dominate Eustatic Sea-Level Rise in the 21st Century

Abstract: Ice loss to the sea currently accounts for virtually all of the sea-level rise that is not attributable to ocean warming, and about 60% of the ice loss is from glaciers and ice caps rather than from the two ice sheets. The contribution of these smaller glaciers has accelerated over the past decade, in part due to marked thinning and retreat of marine-terminating glaciers associated with a dynamic instability that is generally not considered in mass-balance and climate modeling. This acceleration of glacier mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
440
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(458 citation statements)
references
References 13 publications
6
440
0
6
Order By: Relevance
“…As shown explicitly in section 5, the action of such modern ice sheet melting has a significant impact on Earth rotation. Models of modern land ice melting such as those constrained by GRACE itself [e.g., Cazenave et al, 2009;Peltier, 2009] for the polar regions and by Meier et al [2007] for the small ice sheets and glaciers, must be shown to pass the test provided by the GRACE observations. However, the ICE-5G (VM2) model, and the modest improvements to it that are currently under construction, are precisely the models required to filter ice age influence from these modern space geodetic observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown explicitly in section 5, the action of such modern ice sheet melting has a significant impact on Earth rotation. Models of modern land ice melting such as those constrained by GRACE itself [e.g., Cazenave et al, 2009;Peltier, 2009] for the polar regions and by Meier et al [2007] for the small ice sheets and glaciers, must be shown to pass the test provided by the GRACE observations. However, the ICE-5G (VM2) model, and the modest improvements to it that are currently under construction, are precisely the models required to filter ice age influence from these modern space geodetic observations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this positive outcome is based on the assumption that the rotational response of the planet to surface mass load forcing is that based on the recognition that the effective thickness of the elastic lithosphere is zero in the infinite time limit insofar as the rotational response is concerned. An extremely important caveat to this analysis, however, is that the very large contribution to the global rate of sea level rise due to the melting of small ice sheet and glaciers by Meier et al [2007] is accurate. Their inference of the rate that has been active over the period during which the GRACE satellites have been flying is 1.1 mm yr À1 , almost double their earlier estimates [e.g., Dyurgerov and Meier, 1997].…”
Section: Ice-5g (Vm2) Gia Predictions and The Closure Of The Global Smentioning
confidence: 99%
“…The sea-level rise estimates of Meehl et al (2007b), Meier et al (2007), Pfeffer et al (2008) and Radić and Hock (2011) mentioned in the introduction all fall at least partly within this range. The Meehl et al (2007b) estimate is slightly lower than our contribution, which might be caused by our initial GIC volume estimate being higher than their highest volume estimate: 0.50 m SLE vs. 0.37 m SLE.…”
Section: Discussionmentioning
confidence: 96%
“…IPCC AR4 projected a contribution of 0.08-0.15 m sea-level equivalent (SLE) for the A1B scenario (Meehl et al, 2007b), based on a range of climate models and three different values for the initial volume of all glaciers. As a follow-up on IPCC AR4, Meier et al (2007) estimated a GIC contribution of 0.1-0.25 m SLE by 2100, where the range originates from two assumptions for the acceleration of ice loss. Another estimate was presented by Pfeffer et al (2008), who found a GIC contribution of 0.17-0.55 m SLE by 2100, based on kinematically constrained scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…From the mid-1990s to 2000-01 these glaciers lost mass almost twice as rapidly, at a mean rate of about 96 ± 35 km 3 yr À1 w.e., again accounting for roughly 5 to 12% of the observed mean sea-level rise during this recent period of more rapid increase [Arendt et al, 2002]. If global warming continues as projected by the most recent climate model simulations for the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment Report (AR4) [IPCC, 2007], thinning and retreat of these glaciers, as well as other mountain glaciers worldwide, is likely to accelerate [Meier et al, 2007]. There is thus strong motivation to develop quantitative methods for estimating how much melting glaciers are likely to contribute to rising seal level during the 21st century.…”
Section: Introductionmentioning
confidence: 99%